Resistance against Necropolitics: A Study of Shaila Abdullah’s Saffron Dreams - Bhatta, Sita Ram (KMC Journal, 2023)
This paper examines the exercise of necropower by the Americans on the South Asians, especially the Muslims, in the aftermath of 9/11. The purpose of the study is to expose how the Americans (ab)used their social and political power on the lives of the Muslim migrants, making it difficult for them to exist in the host land, that is, the US. For this purpose the study analyzes the narrative data from Sheila Abdullah’s Saffron Dreams (2009). In the novel, the pregnant protagonist Arissa Illahi suffers racial hatred and discrimination while she was undergoing the trauma of losing her husband in the Twin Tower attack of 9/11. Drawing upon the concept of necropolitics by Achille Mbembe, the study discusses how the so-called advanced society of the USA is limited to parochialism of White supremacy. The paper focuses on how the events of ‘September 11’ resulted in the cultural clash between the West and the Muslim world, and how the fighters of the so-called War on Terror were exacerbating the terror through their conduct of Islamophobia. It concludes with a note that one can survive being committed to and taking help of art and creation in spite of social vulnerability.